Are immigrants living in France more reluctant to receive vaccines than native-born French citizens? findings from the national health Barometer study. Issue 28 (21st June 2022) - Moussaoui, Sohela; Combes, Simon; Ibanez, Gladys; Gautier, Arnaud; Relyea, Bridget; Vignier, Nicolas
Highlights: Immigrants in France were less hesitant toward vaccines than the host population. Immigrant participants had the most extreme opinions on vaccination. Opinions on vaccines become negative with time spent in France. Abstract: Background: France is one of the world's most vaccine hesitant countries and vaccine hesitancy (VH) is considered one of the world's leading threats to global health. However, little is known about VH in immigrant populations in France. Using data from the 2016 Health Barometer, we examined VH among newcomers, more established immigrants, and the native-born population in France. Methods: Data was collected from French speaking individuals aged from 15 to 75 years old, residing in France. Individuals were selected through randomly generated landline and mobile phone numbers. Vaccine hesitancy was assessed through four questions and a "time spent in France" variable was created, using the year of arrival in France. Associations were studied using logistic regression. Results: A sample of 15, 216 participants residing in France included 1, 524 foreign-born immigrants and 13, 692 native-born individuals, with a mean age of 46-years. Most participants (75.7%) reported being favorable to vaccination regardless of country of origin but immigrants were less hesitant toward vaccinations than the host population. Foreign-born immigrants from North Africa had the most favorable views whereas those from sub-Saharan Africa held most unfavorable views on vaccination. With time spent in France, the opinions towards vaccination became more negative (aOR = 0.57, 95 %CI [0.40–0.79], p = 0.001) and the risk of vaccine refusal (aOR = 2.34, 95 %CI [1.45 – 3.78] p = 0.001) and reluctant acceptance of vaccines increased (aOR = 1.89 95 %CI [1.20 – 2.99], p = 0.006).Foreign-born individuals with the longest residency in France had more negative opinions than native-born individuals, regardless of region of origin. Conclusion: Immigrants were less hesitant toward vaccinations than the host population, but vaccine hesitancy increased with time spent in France. The provision of appropriate information and awareness to facilitate critical thinking towards antivaccine theories is necessary for immigrants in France.